Street law : a course in practical law - Arbetman, Lee; O'Brien, Edward L.; McMahon, Edward, 1947- (St. Paul : West Pub. Co., 1990)
A law textbook for high school students, designed to give them practical advice, knowledge, and skills to survive in our'law-saturated' society
'A publication of the National Institute for Citizen Education in the Law'
Includes index
Keywords: Law -- United States -- Popular works; Law; Life skills; Consumer education